Relationship between green marketing tools' and consumer's purchase behaviour in Kota Bharu, Kelantan - Sethuraman, Logesh Kumar; Chairullah, Radiah; Hassan, Siti Raihan; Wendy, Wong Hui Hui (2015)
Nowadays consumer are concern about eco-friendly environment and focus on the green product and service. This has been contributing many industries change their production trend to green product and service to meet the need and want of their customers. This is also include imple the manufacturing going green. This research is to investigate the relationship of perception of eco-labelling, perception of eco-brand, environmental advertising and trust in eco-label and eco-brand affect the consumer purchase behaviour. This study surveyed 100 of respondents around Kota Bharu, Kelantan. A convenience sampling was selected because the sample was selected based on the personal judgement of the researcher. The results of finding found that perception of eco-labelling, perception of eco-brand, environmental advertising and trust in eco-label and eco-brand has significant relationship with the consumer purchase behaviour. The limitation of this study was covers the level understanding of consumers towards green marketing tools in Kota Bharu generally and size of sample might not comprehensive enought. The discussion of the finding include give some recommendation for the future study and for manufacturing to improve themselves going to green marketing.